Celebrating Ibn Rushd’s Eight-Hundredth Anniversary - Majid Fakhry (International Institute of Islamic Thought, 1998)
In the context of the world-wide celebrations of the eight-hundrth anniversary of Abu al-Walid Ibn Rushd, known to Western scholars as Averroes (1126-1198), the Tunisian Cultural Foundation (Bayt al- Hikmah) held an International Averroes Symposium, sponsored jointly with UNESCO, in Carthage, Tunis, on February 16 to February 22, 1998. The symposium was hosted by Abd al-Wahab Buhdiba, Director of Bayt al-Hikmah, and was inaugurated by the President of Tunisia, Zayn al-Abidin Ali, who declared 1998 Ibn Rushd’s year. This symposium was attended by a large number of scholars from France, England, Spain, the United States, Iraq, Lebanon, Syria, Morocco, Libya, and Tunisia. It was my good fortune to open the symposium with a lecture titled “Averroes, Aquinas and the Rise of Latin Scholasticism in Western Europe,” in which I tried to highlight the decisive role Ibn Rushd‘s Commentaries on Aristotle played in the rediscovery of Aristotle in Western Europe, the resurgence of interest in Greek-Arabic philosophy, and the consequent rise of Latin Scholasticism. Through translations by such eminent scholars as Michael the Scot and Heman the German during the first decades of the thirteenth century, Ibn Rushd’s work triggered a genuine intellectual revolution in leamed circles. Before long, Latin philosophers and theologians had split into two rival groups, the pro- Averroists, with Siger of Bradbant (d. 1281) at their head, and the anti- Averroists, with St. Thomas Aquinas (d. 1274) at their head. ”he principal issues around which the controversy tumed were the unity of the intellect, the eternity of the world, the immortality of the soul and the denial of divine providence. The confrontaton between the two rival groups became so acute that in 1270, the Bishop of Paris, Etienne ...